Media Matter : Images as Presenters, Mediators, and Means of Observation - Barceló Bauzà, Gabriel; Braster, Sjaak; Comas i Rubí, Francesca; Comas Rubí, Francisca; Fullana Puigserver, Pere; Gelabert Gual, Llorenç; González Gómez, Sara; González Gómez, Sara; Grosvenor, Ian; Herman, Frederik; Kalke, Baiba; Kesteloot, Stefanie; et al. (2022)
This volume discusses a broad range of themes and methodological issues around images, photography and film. It is about sharing a fascination about the visual history of education and how images became the most influential (circulating) media within the field of education on local, regional, national and international levels. Within this volume images are primarily analyzed as presenters, mediators, and means of observation. Images are seen as mobile reproducible media which play an active role within the public and educational sphere. They are means of observation and storytelling, they shape identities by presenting models of how we should act in and perceive the world, they circulate though different contexts and media, all of which impacts their meanings.